SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN SMARTPHONE TERBAIK MENGGUNAKAN METODE SMART (Simple Multi Attribute Rating Technique) BERBASIS WEB - Satria Hudin, Achmada; Putra Eka Prismana, IGL; Mashuri , Chamdan; Kistofer , Terdy (Inovate, 2025)
The implementation of a decision support system will be implemented in a website-based application aimed at making it easier for consumers to get the best smartphone recommendations. The study applied the Simple Multi Attribute Rating Technique method to determine the weighting. on the system and generate data according to the parameters consumer needs. The results of this research are a website-based application that contains recommendations for smartphones that are running effectively and are intended to be used by consumers in the Fast Fund Store as a means to rejuvenate smartphone recommendations as needed. This can be explained by the Simple Multi Attribute Rating Technique's successful use of scaling when an application is running.